Nonaqueous electrolyte secondary battery

By using the improved lithium-containing composite oxide with a surface modification layer as the positive electrode active substance in a nonaqueous electrolyte secondary battery, and optimizing the positive electrode mixture layer and connection method, the problem of uneven reaction distribution after the battery is large-scaled is solved, and high energy density and excellent power characteristics and cycling characteristics are achieved.

CN119836696APending Publication Date: 2025-04-15PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380063456.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-08-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing nonaqueous electrolyte secondary batteries have shortcomings in improving volume energy density, power characteristics and cycle characteristics. Especially after the battery size is larger, the uneven reaction distribution of the positive electrode and the negative electrode leads to an increase in internal resistance and a decrease in characteristics.

Method used

By using lithium-containing composite oxides of the surface modification layer containing Ca and Sr elements as the positive electrode active material and integrating them into the positive electrode mixture layer, the weight of the unit area of ​​the mixture layer reaches 250 g/m2 or more, and the connection method between the positive electrode and the sealing body is optimized to improve the uniformity of the reaction distribution.

Benefits of technology

While achieving high energy density, the internal resistance of the battery is reduced, the power characteristics and cycle characteristics are improved, and the effective performance of batteries with a volume energy density of more than 600Wh/L is ensured in large-scale conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836696A_ABST
    Figure CN119836696A_ABST
Patent Text Reader

Abstract

The non-aqueous electrolyte secondary battery (10) is provided with an electrode body (14) in which a positive electrode (11) and a negative electrode (12) are laminated with a separator interposed therebetween, and an outer case (15) that houses the electrode body (14), the volume energy density of the non-aqueous electrolyte secondary battery (10) being 600 Wh / L or more, the positive electrode (11) including a positive electrode core and a positive electrode mixture layer that is formed on the surface of the positive electrode core and contains a positive electrode active material, and the negative electrode (12) including a positive electrode active material. The positive electrode active material contains a lithium-containing composite oxide having a layered rock salt structure, and a surface modification layer present on the particle surface of the composite oxide, the surface modification layer contains at least one element selected from Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb, and Zr, the weight per unit area of the positive electrode mixture layer is 250 g / m2 or more, and the surface modification layer contains at least one element selected from the group consisting of W, Mo, Ti, Si, Nb, and Zr. The positive electrode (11) is connected with more than three positive electrode leads (19).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art

[0002] In recent years, as a high-power, high-capacity secondary battery, the following non-aqueous electrolyte secondary battery is widely used: it has a positive electrode, a negative electrode and a non-aqueous electrolyte, and allows Li ions and the like to migrate between the positive electrode and the negative electrode to perform charging and discharging. Patent document 1 discloses a secondary battery that improves the power characteristics of the battery by arranging a current collecting member above and below an electrode body with multiple tabs protruding.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 5747082 Summary of the invention

[0006] In recent years, the enlargement of batteries has been studied for the purpose of improving volume energy density. In enlarged batteries, ensuring high volume energy density and improving power characteristics and cycle characteristics are important issues. The existing technologies including Patent Document 1 cannot fully cope with such issues, and there is still a lot of room for improvement.

[0007] A nonaqueous electrolyte secondary battery as one embodiment of the present invention comprises: an electrode body formed by stacking a positive electrode and a negative electrode via a separator, and an outer shell for accommodating the electrode body, wherein the volume energy density of the nonaqueous electrolyte secondary battery is 600Wh / L or more, the positive electrode comprises: a positive electrode core, and a positive electrode mixture layer formed on the surface of the positive electrode core and containing a positive active material, the positive electrode active material comprises: a lithium-containing composite oxide having a layered rock salt structure, and a surface modification layer present on the surface of particles of the composite oxide, the surface modification layer comprises at least one element of Ca and Sr and comprises at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, and the unit area weight of the positive electrode mixture layer is 250g / m 2 In the above, three or more positive electrode leads are connected to the positive electrode.

[0008] In addition, as another embodiment of the present invention, a non-aqueous electrolyte secondary battery comprises: an electrode body formed by stacking a positive electrode and a negative electrode with a separator therebetween, and an outer shell for accommodating the electrode body, wherein the volume energy density of the non-aqueous electrolyte secondary battery is 600Wh / L or more, the positive electrode comprises: a positive electrode core, and a positive electrode mixture layer formed on the surface of the positive electrode core and containing a positive electrode active material, the positive electrode active material comprises: a lithium-containing composite oxide having a layered rock salt structure, and a surface modification layer present on the surface of particles of the composite oxide, the surface modification layer comprises at least one element of Ca and Sr and comprises at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, and the unit area weight of the positive electrode mixture layer is 250g / m 2 As described above, in the electrode assembly, the positive electrode protruding upward from the negative electrode and the separator is connected to the positive electrode current collecting member, and the positive electrode lead is led out from the positive electrode current collecting member.

[0009] According to the nonaqueous electrolyte secondary battery which is one embodiment of the present disclosure, high energy density can be achieved, and power characteristics and cycle characteristics can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0011] Figure 2 To show the structure in an expanded state Figure 1 A front view of a positive electrode and a negative electrode of an electrode assembly included in a nonaqueous electrolyte secondary battery.

[0012] Figure 3 It is a plan view showing the position where the positive electrode lead is arranged on the upper surface of the electrode body.

[0013] Figure 4 It is a longitudinal cross-sectional view of a nonaqueous electrolyte secondary battery as another example of the embodiment.

[0014] Figure 5 for Figure 4 1 is a perspective view of an electrode body provided in a non-aqueous electrolyte secondary battery, and is a view showing the configuration of a positive electrode, a negative electrode, and a separator in a state where the vicinity of the outer end of a roll is unfolded. DETAILED DESCRIPTION

[0015] In recent years, the enlargement of battery size has been studied for the purpose of improving volume energy density. By enlarging the battery size, the volume of the positive electrode and the negative electrode can be relatively larger than the volume of the part that is not conducive to charging and discharging, compared with the existing small-sized battery. That is, the proportion of the positive electrode and the negative electrode in the battery can be increased.

[0016] However, if the battery size is excessively enlarged, the reaction of the positive and negative electrodes in the electrode plates will be offset. Specifically, near the position where the positive lead is connected, the charge and discharge reaction is promoted. On the other hand, in the position away from the position where the positive lead is connected, there is a tendency that the charge and discharge reaction becomes less likely to occur. As a result, the effective reaction area of ​​the positive and negative electrodes is reduced, thereby increasing the internal resistance of the battery and reducing the power characteristics. In addition, near the position where the positive lead is connected, the charge and discharge reaction is promoted, and therefore, it is also easy to produce a reduction in cycle characteristics. The above phenomenon is obvious in batteries with a volume energy density of 600Wh / L or more.

[0017] In order to solve this problem, the inventors conducted in-depth research and found that: by using a lithium-containing composite oxide containing at least one element of Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, the surface modification layer is present on the particle surface as a positive electrode active material, thereby improving the cycle characteristics. It is speculated that this is because the corrosion and degradation of the lithium-containing composite oxide caused by the side reaction with the non-aqueous electrolyte are effectively suppressed by the surface modification layer, and the cycle characteristics are improved.

[0018] The inventors conducted further research and found that by setting the weight per unit area of ​​the positive electrode mixture layer containing the positive electrode active material to 250 g / m 2 As described above, the positive electrode and the sealing body are connected in a prescribed manner, thereby maintaining the volume energy density and cycle characteristics, and the power characteristics are improved. By making the connection between the positive electrode and the sealing body in a prescribed manner, the distribution of the reaction of the positive electrode in the electrode plate is made more uniform, and the effective reaction area of ​​the positive electrode is increased. It is speculated that as a result, the internal resistance of the battery is reduced and the power characteristics are improved. It is also speculated that by using a lithium-containing composite oxide with a surface modification layer for the positive electrode active material, the migration of Li between the positive electrode active material and the electrolyte is promoted, and the reaction resistance in the positive electrode is reduced. As a result, the internal resistance of the battery is reduced and the power characteristics are further improved. As a result, in a battery with a volume energy density of 600Wh / L or more, by making the unit area weight of the positive electrode mixture layer containing the above-mentioned positive electrode active material 250g / m 2 As described above, by making the connection between the positive electrode and the sealing body a predetermined form, a high energy density can be achieved, and the power characteristics and cycle characteristics can be improved.

[0019] Below, refer to Figure 1 to Figure 3An example of an embodiment of the non-aqueous electrolyte secondary battery of the present invention is described in detail. In the following description, as an example of an embodiment of the non-aqueous electrolyte secondary battery of the present invention, a non-aqueous electrolyte secondary battery in which a wound electrode body is housed in an outer shell with a bottomed cylindrical shape is exemplified, but the battery may also be a square battery with a square outer shell with a bottomed cylindrical shape. In addition, in this specification, when the term "roughly" is used, it is used in the same meaning as the term "approximately", and the feature of "roughly to" is satisfied as long as it is substantially the same. It should be noted that the structure formed by selectively combining the various constituent elements of the multiple embodiments and modified examples described below is included in the scope of the present disclosure.

[0020] Figure 1 FIG. 2 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 comprises: a wound electrode body 14, a nonaqueous electrolyte, and an outer case 15 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 comprises a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The opening of the outer case 15 is blocked by a sealing body 16. In the following, for the sake of convenience of description, the sealing body 16 side of the battery is referred to as the upper side, and the bottom side of the outer case 15 is referred to as the lower side.

[0021] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof are used in the non-aqueous solvent. As an example of a non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof can be cited. The non-aqueous solvent can also contain a halogen substitute (for example, fluoroethylene carbonate, etc.) formed by replacing at least a portion of the hydrogen of these solvents with a halogen atom such as fluorine. For example, lithium salts such as LiPF6 are used in the electrolyte salt.

[0022] The positive electrode 11, the negative electrode 12 and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked along the radial direction of the electrode body 14 by spiral winding. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 19 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 20 connected to the negative electrode 12 by welding or the like.

[0023] Insulating plates 17 and 18 are provided above and below the electrode body 14, respectively. The positive lead 19 extends upward and downward through the through hole of the insulating plate 17, connecting the bottom plate of the sealing body 16, that is, the partially opened metal plate 22, to the positive electrode 11 contained in the electrode body 14. Thus, the positive electrode 11 is connected to the sealing body 16, and the top plate of the sealing body 16, that is, the cover 26, which is electrically connected to the partially opened metal plate 22, becomes the positive terminal. The positive lead 19 is, for example, an aluminum lead. On the other hand, the negative lead 20 extends to the bottom side of the outer shell 15 through the through hole of the insulating plate 18 and is welded to the bottom inner surface of the outer shell 15. Thus, the negative electrode 12 is connected to the outer shell 15, and the outer shell 15 becomes the negative terminal. The negative lead 20 is, for example, a nickel lead.

[0024] Three positive electrode leads 19 are connected to the positive electrode 11. As a result, the connection resistance between the positive electrode 11 and the sealing body 16 is reduced, and the power characteristics of the non-aqueous electrolyte secondary battery 10 can be improved. Figure 1 The middle figure shows only one of the three positive leads. The number of positive leads 19 connecting the positive electrode 11 and the sealing body 16 can be more than three. The more positive leads 19 there are, the less the connection resistance is, but the more the cost increases. Therefore, from the perspective of both the effect of reducing the connection resistance and the cost, the number of positive leads 19 is preferably more than 3 and less than 10, more preferably more than 3 and less than 8, and particularly preferably more than 3 and less than 6. It should be noted that the more than three positive leads 19 connected to the positive electrode 11 can be directly connected to the sealing body 16, or can be connected to the sealing body 16 via a collector member. In addition, there is no particular limitation on the method of connecting the negative electrode 12 to the outer shell 15, and it can be connected with multiple negative leads 20.

[0025] The outer shell 15 is a bottomed cylindrical shape with an outer diameter of 25 mm or more. The outer diameter of the outer shell 15 is preferably 30 mm or more, more preferably 35 mm or more. In addition, the outer diameter of the outer shell 15 can be 38 mm or more, 40 mm or more, 45 mm or more, or 50 mm or more. The outer diameter of the outer shell 15 can be, for example, 60 mm or less. If it is within this range, the volume energy density of the non-aqueous electrolyte secondary battery 10 can be improved. The thickness of the outer shell 15 is, for example, 0.1 mm to 2 mm. The inner diameter of the outer shell 15 is preferably 24 mm or more, more preferably 29 mm or more, and particularly preferably 34 mm or more. In addition, the inner diameter of the outer shell 15 can be 37 mm or more, 39 mm or more, 44 mm or more, or 49 mm or more. The outer shell 15 is, for example, a metal outer can.

[0026] A gasket 27 is provided between the outer shell 15 and the sealing body 16 to ensure the airtightness of the inside of the non-aqueous electrolyte secondary battery 10. The outer shell 15 has, for example, a groove portion 21 formed by pressing the side surface from the outside to support the sealing body 16. The groove portion 21 is preferably formed in an annular shape along the circumferential direction of the outer shell 15, and the sealing body 16 is supported by its upper surface.

[0027] The sealing body 16 has a partially open metal plate 22, a lower valve body 23, an insulating member 24, an upper valve body 25 and a cover 26, which are stacked in sequence from the electrode body 14 side. The components constituting the sealing body 16 have, for example, a disc shape or a ring shape, and the components except the insulating member 24 are electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective central portions, and an insulating member 24 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, for example, the lower valve body 23 breaks, whereby the upper valve body 25 expands toward the cover 26 side and moves away from the lower valve body 23, whereby the electrical connection between the two is cut off. When the internal pressure rises further, the upper valve body 25 breaks, and the gas is discharged from the opening 26a of the cover 26.

[0028] Next, refer to Figure 2 and Figure 3 At the same time, the connection method between the positive electrode 11 and the positive electrode lead 19 is described. Figure 2 To show the structure in an expanded state Figure 1 FIG. 1 is an example of a front view of a positive electrode 11 and a negative electrode 12 of an electrode body 14 included in a nonaqueous electrolyte secondary battery 10 . Figure 3 for Figure 1 FIG. 1 is an example of a top view of an electrode body 14 included in the nonaqueous electrolyte secondary battery 10 .

[0029] The positive electrode 11 includes a positive electrode core body 30 and a positive electrode mixture layer 32 formed on the surface of the positive electrode core body 30 . The negative electrode 12 includes a negative electrode core body 40 and a negative electrode mixture layer 42 formed on the surface of the negative electrode core body 40 .

[0030] Positive electrode 11 Figure 2 As shown, an exposed portion 34 is provided in which a portion of the positive electrode core 30 in the width direction of the positive electrode 11 is exposed. A plurality of exposed portions 34 are arranged along the length direction of the positive electrode. The positive electrode mixture layer 32 is present between the exposed portions 34 throughout the width direction. Thus, the area of ​​the positive electrode core exposed portion 34 for stably connecting the positive electrode lead 19 to the positive electrode core 30 can be ensured, and the area of ​​the positive electrode mixture layer 32 can be increased. As a result, the internal resistance of the non-aqueous electrolyte secondary battery 10 is reduced and the power characteristics are improved. In addition, one of the positive electrode leads 19 is connected to each of the exposed portions 34 of the positive electrode core.

[0031] Negative electrode 12 Figure 2As shown, an exposed portion 44 where the negative electrode core 40 is exposed is provided at the inner end of the roll in the longitudinal direction. The negative electrode lead 20 is connected to the exposed portion 44.

[0032] In addition, if Figure 2 As shown, the three positive electrode leads can be connected to the positive electrode 11 at substantially equal intervals in the longitudinal direction of the positive electrode 11. As a result, the deviation of the reaction in the longitudinal direction of the positive electrode 11 during charge and discharge is suppressed, and the area of ​​the positive electrode 11 that contributes to the reaction during charge and discharge can be increased. As a result, the internal resistance of the nonaqueous electrolyte secondary battery 10 is reduced, and the power characteristics are improved.

[0033] In addition, if Figure 3 As shown in FIG. 1 , the three positive electrode leads 19 can be arranged so that the central angles formed by the radial direction lines passing through the circumferential center of the positive electrode leads 19 are substantially equal. As a result, the deviation of the reaction in the longitudinal direction of the positive electrode 11 during charge and discharge is suppressed, and the area of ​​the positive electrode 11 that contributes to the reaction during charge and discharge can be increased. As a result, the internal resistance of the nonaqueous electrolyte secondary battery 10 is reduced, and the power characteristics are improved. In addition, by Figure 3 By connecting the positive electrode leads 19 in the manner shown, each positive electrode lead 19 can be easily joined to the partially opened metal plate 22 without being blocked by other positive electrode leads 19 .

[0034] Below, refer to Figure 4 and Figure 5 Another embodiment of the cylindrical secondary battery disclosed in the present invention will be described in detail. Figure 1 The same components as those in the embodiment shown are marked Figure 1 The same reference numerals as those in the embodiments shown in the drawings are used, and the description thereof is omitted. Figure 1 The same functions, effects and modifications as those of the embodiment shown are described below.

[0035] Figure 4 In another example of the implementation method, Figure 1 Figure. Figure 4 As shown, the upper end of the positive electrode 11 contained in the electrode body 14 is connected to the positive electrode current collecting member 50, and the positive electrode current collecting member 50 is connected to the sealing body 16 by the positive electrode lead 19. As a result, the positive electrode 11 is connected to the sealing body 16, and the top plate of the sealing body 16, that is, the cover 26, which is electrically connected to the partially opened metal plate 22, becomes the positive terminal. Figure 1 The embodiment shown is also connected to the outer shell 15 by the negative electrode lead 20. It should be noted that the negative electrode 12 is connected to the outer shell 15. Figure 4 The positive electrode 11 of the illustrated embodiment is similarly connected to the negative electrode 12 and the negative electrode current collecting member, and the negative electrode current collecting member and the outer case 15 may be connected by a negative electrode lead 20 .

[0036] The positive electrode current collecting member 50 is not particularly limited in material and shape as long as it can be connected to the positive electrode 11 and the sealing body 16. For example, it can be a disc-shaped member made of aluminum. In addition, the positive electrode current collecting member 50 can have a single hole or multiple holes at any position from the perspective of electrolyte circulation.

[0037] Next, refer to Figure 5 At the same time, the structure of the electrode body 14 will be described. Figure 5 for Figure 4 1 is a perspective view of an electrode body 14 in a non-aqueous electrolyte secondary battery 10 shown in FIG. 1 , and is a view showing the structure of a positive electrode 11, a negative electrode 12, and a separator 13 in a state where the outer end of the roll is unfolded. In the electrode body 14, the positive electrode 11 protrudes upward more than the negative electrode 12 and the separator 13. Thus, the upper end of the positive electrode 11 is connected to the positive electrode current collecting member 50. The positive electrode 11 has an exposed portion 34 where the positive electrode core 30 is exposed at the upper end. That is, the exposed portion 34 is connected to the positive electrode current collecting member 50. Thus, the positive electrode 11 and the positive electrode current collecting member 50 can be connected more reliably.

[0038] Hereinafter, the positive electrode 11, the negative electrode 12 and the separator 13 constituting the electrode body 14, in particular the positive electrode 11 will be described in detail. It should be noted that the positive electrode 11, the negative electrode 12 and the separator 13 described below can also be applied to any of the above-mentioned embodiments.

[0039] [positive electrode]

[0040] The positive electrode 11 includes a positive electrode core 30 and a positive electrode mixture layer 32 formed on the surface of the positive electrode core 30. The positive electrode mixture layer 32 is preferably formed on both surfaces of the positive electrode core 30. The positive electrode core 30 may be made of a foil of a metal such as aluminum or an aluminum alloy that is stable within the potential range of the positive electrode 11, or a thin film having the metal disposed on the surface.

[0041] The positive electrode mixture layer 32 contains a positive electrode active material. In addition, the positive electrode mixture layer 32 may further contain a conductive agent, a binder, etc. The positive electrode mixture layer 32 can be produced, for example, by applying a positive electrode slurry containing a positive electrode active material, a conductive agent, a binder, etc. on the surface of the positive electrode core 30, drying the coating, and then rolling it.

[0042] The weight per unit area of ​​the positive electrode mixture layer 32 is 250 g / m 2 As a result, the volume energy density of the non-aqueous electrolyte secondary battery 10 can be improved. From the viewpoint of improving the volume energy density, the unit area weight of the positive electrode mixture layer 32 only needs to be 250 g / m 2If the weight per unit area of ​​the positive electrode mixture layer 32 is too large, the cycle characteristics of the non-aqueous electrolyte secondary battery 10 tend to be reduced. Therefore, the weight per unit area of ​​the positive electrode mixture layer 32 is preferably 600 g / m 2 Below, more preferably 500g / m 2 Therefore, an example of a suitable range of the weight per unit area of ​​the positive electrode mixture layer 32 is 250 g / m 2 Above and 600g / m 2 The thickness of the positive electrode mixture layer 32 is, for example, 10 μm or more and 150 μm or less on one side of the positive electrode core body 30 .

[0043] The positive electrode active material contained in the positive electrode mixture layer 32 includes a lithium-containing composite oxide having a layered rock salt structure. As the layered rock salt structure of the lithium-containing composite oxide, for example, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be cited. From the viewpoint of high capacity and stability of the crystal structure, the lithium-containing composite oxide preferably has a layered rock salt structure belonging to the space group R-3m. The layered rock salt structure of the lithium-containing composite oxide may also include a transition metal layer and a Li layer.

[0044] The lithium-containing composite oxide includes, for example, secondary particles formed by aggregation of primary particles. The particle size of the primary particles constituting the secondary particles is, for example, 0.02 μm or more and 2 μm or less. The particle size of the primary particles is measured as the diameter of a circumscribed circle in a particle image observed by a scanning electron microscope (SEM).

[0045] The average particle size of the secondary particles of the lithium-containing composite oxide is, for example, 2 μm or more and 30 μm or less. Here, the average particle size refers to the median particle size (D50) based on the volume. D50 refers to the particle size at which the cumulative frequency of the particle size distribution based on the volume becomes 50% from the particle with the smaller particle size, also known as the median diameter. The particle size distribution of the secondary particles can be measured using a laser diffraction particle size distribution measuring device (e.g., MicrotracBEL Corp., MT3000II) with water as the dispersion medium.

[0046] From the viewpoint of high capacity, the lithium-containing composite oxide contains Ni in an amount of preferably 70 mol% or more, more preferably 80 mol% or more, relative to the total molar number of metal elements other than Li. The content of Ni may be 85 mol% or more, or 90 mol% or more relative to the total molar number of metal elements other than Li. The upper limit of the Ni content is, for example, 95 mol%.

[0047] The lithium-containing composite oxide can be given by the general formula Li a Ni x Co y Alz Mn w M1 v O 2-b (wherein, 0.95≤a≤1.05, 0.7≤x≤0.95, 0≤y≤0.15, 0≤z≤0.1, 0≤w≤0.3, 0≤v≤0.1, 0≤b≤0.05, x+y+z+w+v=1, M1 contains at least one element selected from Fe, Ti, Si, Nb, Zr, Mo, W and Zn). It should be noted that the positive electrode active material may also contain lithium-containing composite oxides or other compounds other than those shown in the above general formula within the scope of not impairing the purpose of the present disclosure. The molar fraction of the metal element contained in the entire particle of the lithium-containing composite oxide is determined by inductively coupled plasma (ICP) emission spectrometry analysis.

[0048] The surface modification layer is present on the particle surface of the lithium-containing composite oxide. Specifically, the surface modification layer is present on at least one of the surface of the secondary particles of the lithium-containing composite oxide and the interface between the primary particles. The surface modification layer may exist in a dotted manner to cover at least a portion of the particle surface of the lithium-containing composite oxide, or may exist in a manner to cover the entire surface of the particle.

[0049] The surface modification layer contains at least one element of Ca and Sr and contains at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. Specifically, the surface modification layer, for example, contains a compound containing at least one element of Ca and Sr and containing at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. In addition, the surface modification layer, for example, contains: a compound containing at least one element of Ca and Sr and a compound containing at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. By making the surface modification layer present on the particle surface of the lithium-containing composite oxide, the corrosion and deterioration of the lithium-containing composite oxide caused by the side reaction with the electrolyte are effectively suppressed. As a result, the cycle characteristics of the non-aqueous electrolyte secondary battery 10 are improved. In addition, by making the surface modification layer present on the particle surface of the lithium-containing composite oxide, the migration of Li between the positive electrode active material and the electrolyte is promoted, and the reaction resistance in the positive electrode is reduced. As a result, the internal resistance of the battery is reduced and the power characteristics are further improved.

[0050] Examples of the compound containing at least one element of Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr include: x B y O z(wherein, 1≤x≤2, 1≤y≤5, 4≤z≤9, A is at least one selected from Ca and Sr, and B is at least one selected from W, Mo, Ti, Si, Nb and Zr) (hereinafter referred to as “A x B y O z Compounds”).

[0051] As A x B y O z Specific examples of the compounds include CaWO4, CaMoO3, CaMoO4, CaTiO3, Ca2TiO4, CaSiO3, Ca2SiO4, CaNbO3, CaNb2O6, CaZrO3, CaZr4O9, SrWO4, SrMoO3, SrMoO4, SrTiO3, Sr2TiO4, SrSiO3, Sr2SiO4, SrNbO3, SrNb2O6, SrZrO3, and SrZr4O9.

[0052] A x B y O z The presence of the compound can be confirmed by using synchrotron X-ray diffraction measurements. x B y O z The compound may be present in a dotted form so as to cover at least a portion of the surface of the particles of the lithium-containing composite oxide, or may be present so as to cover the entire surface of the particles.

[0053] Specific examples of compounds containing Ca include Ca(OH)2, CaO, CaCO3, CaSO4, and Ca(NO3)2. Specific examples of compounds containing Sr include Sr(OH)2, Sr(OH)2·8H2O, Sr(OH)2·H2O, SrO, SrCO3, SrSO4, and Sr(NO3)2. Specific examples of compounds containing at least one element selected from the group consisting of W, Mo, Ti, Si, Nb, and Zr include oxides, hydroxides, carbonates, and sulfates containing at least one element selected from the group consisting of W, Mo, Ti, Si, Nb, and Zr.

[0054] The total amount of Ca and Sr contained in the surface modification layer is preferably 5 mol% or less relative to the total molar amount of metal elements other than Li in the lithium-containing composite oxide. The lower limit of the total amount of Ca and Sr is, for example, 0.001 mol%.

[0055] The total amount of W, Mo, Ti, Si, Nb and Zr contained in the surface modification layer is preferably 5 mol% or less relative to the total molar amount of metal elements other than Li in the lithium-containing composite oxide. The lower limit of the total amount of W, Mo, Ti, Si, Nb and Zr is, for example, 0.001 mol%.

[0056] The presence of the surface modification layer on the surface of the lithium-containing composite oxide particles and the total amount of metal elements contained in the surface modification layer can be confirmed by measuring the cross section of the lithium-containing composite oxide particles using TEM-EDX (transmission microscopy-energy dispersive X-ray spectroscopy).

[0057] The positive electrode mixture layer 32 may contain other positive electrode active materials in addition to the positive electrode active material of the present embodiment. Examples of other positive electrode active materials include lithium-containing composite oxides having no surface modification layer on the particle surfaces.

[0058] In addition, the conductive agent contained in the positive electrode mixture layer 32 preferably includes carbon fibers. In the positive electrode mixture layer 32, the content of carbon fibers can be 0.01 mass % or more and 1 mass % or less relative to the total mass of the positive electrode active material. It is therefore believed that ensuring the conductive path of the positive electrode mixture layer 32 contributes to the improvement of the cycle characteristics. When the content of carbon fibers is less than 0.01 mass %, the conductive path of the positive electrode mixture layer 32 cannot be fully ensured. In addition, if the content of carbon fibers becomes greater than 1 mass %, it is easy to hinder the migration of the electrolyte in the positive electrode mixture layer 32, which is easy to cause a decrease in durability.

[0059] As carbon fibers, there can be mentioned known materials used as conductive agents for batteries, for example, carbon nanotubes (CNTs), carbon nanofibers (CNFs), vapor deposited carbon fibers (VGCFs), electrospun carbon fibers, polyacrylonitrile (PAN)-based carbon fibers, pitch-based carbon fibers, etc.

[0060] In the carbon fiber of the above example, for example, in terms of further suppressing the capacity reduction associated with the charge and discharge cycle, the carbon fiber preferably includes a carbon nanotube (CNT). As CNT, single-layer carbon nanotubes (SWCNT) and multi-layer carbon nanotubes (MWCNT) can be cited. Single-layer carbon nanotubes (SWCNT) show a carbon nanostructure composed of a layer of graphene sheets to form a cylindrical shape, and multi-layer carbon nanotubes are carbon nanostructures composed of more than two layers of graphene sheets stacked in concentric circles to form a cylindrical shape. It should be noted that graphene sheets refer to layers where the carbon atoms of the sp2 hybrid orbits constituting the crystals of graphite (graphite) are located at the vertices of the regular hexagonal type. The shape of the carbon nanotube is unlimited. As the above-mentioned shape, various forms including needle-shaped, cylindrical tubular, fishbone-shaped (fishbone or cup-shaped stacked type), card (trump)-shaped (thin sheet) and coil-shaped can be cited.

[0061] In addition, the conductive agent contained in the positive electrode mixture layer 32 preferably contains amorphous carbon. In the positive electrode mixture layer 32, the content of amorphous carbon may be 1% by mass to 3% by mass relative to the total mass of the positive electrode active material. Thereby, the conductivity between the positive electrode active material particles is improved, and the power characteristics of the battery may be improved. Examples of the amorphous carbon include carbon materials such as carbon black (CB), acetylene black (AB), Ketjen black, and graphite. They may be used alone or in combination of two or more.

[0062] The positive electrode mixture layer 32 may further contain Li2NiO2. Li2NiO2 contains a large amount of Li and functions as a Li filling agent for supplying Li ions to the negative electrode 12 during the first charge and discharge. Li2NiO2 may have a structure identified as the space group Immm.

[0063] The mass of Li2NiO2 contained in the positive electrode mixture layer 32 may be 1% by mass to 10% by mass relative to the total mass of the positive electrode active material contained in the positive electrode mixture layer 32. If the mass of Li2NiO2 contained in the positive electrode mixture layer 32 is 1% by mass or more, a sufficient amount of Li ions can be supplied to the negative electrode 12. In addition, as will be described later, at least a part of Li2NiO2 becomes a compound represented by the general formula Li a Ni 2-a O2 (0 < a ≤ 0.5). When the mass of Li2NiO2 contained in the positive electrode mixture layer 32 is greater than 10% by mass, there is a tendency for the battery capacity to decrease. This is because the contribution of the compound represented by the general formula Li a Ni 2-a O2 (0 < a ≤ 0.5) to the charge-discharge capacity is smaller than that of the lithium-containing composite oxide.

[0064] Part or all of Li2NiO2 after the first charge and discharge becomes, for example, a compound represented by the general formula Li a Ni 2-a O2 (0 < a ≤ 0.5). That is, the positive electrode mixture layer 32 may further contain a compound represented by the general formula Li a Ni 2-a O2 (0 < a ≤ 0.5). Li a Ni 2- a O2 (0 < a ≤ 0.5) releases and stores Li ions during charge and discharge and functions as a positive electrode active material.

[0065] Li a Ni 2-aThe mass of the compound represented by O2(0 < a ≤ 0.5) may be 0.1% by mass to 5% by mass relative to the total mass of the positive electrode active material contained in the positive electrode mixture layer 32. The general formula Li contained in the positive electrode mixture layer 32 a Ni 2-a If the mass of the compound represented by O2(0 < a ≤ 0.5) is 0.1% by mass or more, a sufficient amount of Li ions can be supplied to the negative electrode. In addition, when the mass of the compound represented by the general formula Li a Ni 2-a O2(0 < a ≤ 0.5) contained in the positive electrode mixture layer 32 is more than 5% by mass, there is a tendency for the battery capacity to decrease. This is because the contribution of the compound represented by the general formula Li a Ni 2-a O2(0 < a ≤ 0.5) to the charge-discharge capacity is less than that of the lithium-containing composite oxide.

[0066] The positive electrode mixture layer 32 may further contain a binder. Examples of the binder contained in the positive electrode mixture layer 32 include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyimide-based resins, acrylic resins, polyolefin-based resins, and polyacrylonitrile (PAN). They may be used alone or in combination of two or more.

[0067] Next, an example of a method for manufacturing a positive electrode active material in which the surface modification layer contains a compound of A x B y O z in the present embodiment will be described.

[0068] The manufacturing process of the positive electrode active material includes the following processes: a mixing process in which a composite oxide and a Li compound are mixed to obtain a mixture; a firing process in which the mixture is fired to obtain a lithium-containing composite oxide; and a water washing process in which the fired product is washed with water and heated and dried. By adding a raw material containing element A and a raw material containing element B in the mixing process, a surface modification layer can be formed on the surface of the particles of the lithium-containing composite oxide.

[0069] In the mixing process, for example, a metal oxide containing 70 mol% or more and 95 mol% or less of Ni, 0 mol% or more and 15 mol% or less of Co, and 0 mol% or more and 25 mol% or less of Mn is mixed with a Li compound, a raw material containing element A, and a raw material containing element B to obtain a mixture.

[0070] The metal oxide can be obtained, for example, by stirring a solution of a metal salt containing Ni and any metal element (Co, Mn, etc.), dripping an alkaline solution such as sodium hydroxide, adjusting the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (coprecipitating) a composite hydroxide containing Ni and any metal element, and heat-treating the composite hydroxide. The heat treatment temperature is not particularly limited, for example, in the range of 250°C to 600°C.

[0071] As the Li compound, for example, Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, LiF, etc. In order to easily adjust the above parameters to the above-defined ranges, the mixing ratio of the metal oxide and the Li compound is preferably set to a ratio in which the molar ratio of the total amount of the metal element in the metal oxide to Li is in the range of 1:0.98 to 1:1.1.

[0072] As an example of a raw material containing element A, Ca(OH)2, CaO, CaCO3, CaSO4, Ca(NO3)2, Sr(OH)2, Sr(OH)2·8H2O, Sr(OH)2·H2O, SrO, SrCO3, SrSO4, Sr(NO3)2, etc. can be cited. It should be noted that in order to reduce the amount of moisture generated during calcination, it can be used after drying and dehydration. In addition, these compounds can be crushed to a particle size of 0.1 μm or more and 20 μm or less.

[0073] As an example of a raw material containing element B, hydroxides, oxides, carbonates, sulfates, nitrates, etc. of element B can be cited. It should be noted that in order to reduce the amount of moisture generated during firing, it can be used after drying and dehydration. In addition, these compounds can be crushed to a particle size of 0.1 μm or more and 20 μm or less.

[0074] The metal oxide and the raw material containing element A are preferably mixed at a ratio of, for example, the total amount of the metal element in the metal oxide to the molar ratio of element A of 1:0.0001 to 1:0.02. When a plurality of raw materials containing element A are used, they are mixed in such a manner that the total amount of element A contained in the compound satisfies the ratio. The suitable mixing ratio with the metal oxide is also the same for the raw material containing element B.

[0075] The combustion process is, for example, a multi-stage firing process, which includes at least the following processes: a first firing process of firing at a temperature of 300°C to 680°C under an oxygen gas flow; and a second firing process of firing the fired product obtained by the first firing process at a temperature exceeding 680°C under an oxygen gas flow. In the first firing process, the temperature is increased to a first set temperature of 680°C or less at a first heating rate of 0.2°C / min to 4.5°C / min or less. In the second firing process, the temperature is increased to a second set temperature of 900°C or less at a temperature of 0.5°C / min to 3.5°C / min or less. It should be noted that the first and second heating rates can be set multiple times in each temperature range as long as they are within the above-defined range.

[0076] The holding time of the first set temperature in the first firing step is preferably less than 5 hours, more preferably less than 3 hours. The holding time of the first set temperature refers to the time for maintaining the first set temperature after reaching the first set temperature, and the holding time may be zero. The holding time of the second set temperature in the second firing step is preferably 1 hour to 10 hours, more preferably 1 hour to 5 hours. The holding time of the second set temperature refers to the time for maintaining the second set temperature after reaching the second set temperature. The firing of the mixture is carried out, for example, in an oxygen gas flow with an oxygen concentration of 60% or more, and the flow rate of the oxygen gas flow is reduced relative to every 10 cm 3 The firing furnace is set to 0.2 mL / min or more and 4 mL / min or less, or 0.3 L / min or more per 1 kg of the mixture.

[0077] In the water washing process, the burnt product obtained in the firing process is washed with water to remove impurities, and the washed burnt product is heated and dried. The burnt product is crushed, classified, etc. as needed, and the D50 of the positive electrode active material is adjusted to the target range. The drying of the washed burnt product can be carried out at a temperature below 100°C. An example of a suitable drying temperature is above 150°C and below 600°C. The drying treatment can be carried out under vacuum, in an oxygen gas flow, or in the atmosphere. An example of the drying treatment time is above 1 hour and below 5 hours. Me raw material can be added to the filter cake-like composition after washing or during the heating and drying process. Examples of Me raw materials added after water washing or during the heating and drying process include tungsten oxide (WO3), lithium tungstate (Li2WO4, Li4WO5, Li6W2O9), boric acid (H3BO3), lithium borate (Li2B4O7, Li3BO3, LiB3O5, LiBO2), aluminum oxide (Al2O3), and aluminum sulfate (Al2(SO4)3).

[0078] [negative electrode]

[0079] The negative electrode 12 has a negative electrode core 40 and a negative electrode mixture layer 42 formed on the surface of the negative electrode core 40. The negative electrode mixture layer 42 is preferably formed on both sides of the negative electrode core 40. For the negative electrode core 40, foils of metals such as copper and copper alloys that are stable within the potential range of the negative electrode 12, thin films with such metals disposed on the surface layer, etc. can be used. The negative electrode mixture layer 42 can contain a negative electrode active material and a binder. For example, the thickness of the negative electrode mixture layer 42 on one side of the negative electrode core 40 is 10 μm or more and 150 μm or less. The negative electrode 12 can be fabricated, for example, as follows: A negative electrode slurry containing a negative electrode active material, a binder, etc. is coated on the surface of the negative electrode core 40, and after the coating film is dried, calendering is performed to form the negative electrode mixture layer 42 on both sides of the negative electrode core 40, thereby enabling fabrication.

[0080] As the negative electrode active material contained in the negative electrode mixture layer 42, there is no particular limitation as long as it can reversibly store and release lithium ions, and carbon materials such as graphite are generally used. The graphite can be natural graphite such as flake graphite, massive graphite, and earthy graphite, artificial graphite such as massive artificial graphite and graphitized mesophase carbon microbeads, etc., all of which are acceptable. Additionally, as the negative electrode active material, metals alloyed with Li such as Si and Sn, metal compounds containing Si, Sn, etc., lithium titanium composite oxides, etc. can be used. Further, those provided with a carbon coating film thereon can also be used. For example, Si-containing compounds represented by SiO x (0.5 ≤ x ≤ 1.6), or Li 2y SiO (2+y) Si-containing compounds in which fine particles of Si are dispersed in a lithium silicate phase represented by (0 < y < 2) etc. can be used in combination with graphite.

[0081] As the binder contained in the negative electrode mixture layer 42, for example, styrene-butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salts, polyacrylic acid (PAA) or its salts (which can be PAA-Na, PAA-K, etc., and partially neutralized salts), polyvinyl alcohol (PVA), etc. can be cited. They can be used alone as one kind, or two or more kinds can be used in combination.

[0082] [Separator]

[0083] A porous sheet having ion permeability and insulation is used in the separator 13. As specific examples of the porous sheet, microporous films, woven fabrics, non-woven fabrics, etc. can be cited. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can have a single-layer structure or a multi-layer structure. Additionally, a resin layer with high heat resistance such as an aromatic polyamide resin can be formed on the surface of the separator 13.

[0084] A filler layer containing an inorganic filler may be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13. Specific embodiments

[0086] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.

[0087] <Example 1>

[0088] [Preparation of positive electrode active material]

[0089] The [Ni 0.70 Co 0.15 Mn 0.15 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain a metal oxide (Ni 0.70 Co 0.15 Mn 0.15 O2). Next, Ca(OH)2, MoO3 and WO3 are added to the above metal oxides in such a manner that the molar ratio of Ca is 0.4 mol%, the molar ratio of Mo is 0.2 mol% and the molar ratio of W is 0.2 mol% relative to the total amount of Ni, Co and Mn. Furthermore, lithium hydroxide monohydrate (LiOH·H2O) is mixed in such a manner that the molar ratio of Li is 103 mol% relative to the total amount of Ni, Co, Mn, Ca and W to obtain a mixture (mixing process). For the mixture, under an oxygen gas flow with an oxygen concentration of 95% (a flow rate of 5 L / min per 1 kg of the mixture), the mixture is calcined from room temperature to 650°C at a heating rate of 2.0°C / min, and then calcined from 650°C to 740°C at a heating rate of 0.5°C / min to obtain a calcined product (combustion process). Then, the lithium-containing composite oxide is washed with water and dried to obtain the positive electrode active material of Example 1 (water washing process).

[0090] The obtained positive electrode active material was measured using an ICP emission spectrometer (manufactured by Thermo Fisher Scientific, iCAP6300). As a result, the elements shown in Table 1 described below were confirmed as elements other than Li, O and impurity elements. In addition, the compounds present in the positive electrode active material were identified by synchrotron radiation X-ray diffraction measurement, and the results were as follows: x B y O z Compounds, the presence of CaMoO4 and CaWO4 were confirmed.

[0091] [Production of positive electrode]

[0092] 100% by mass of the positive electrode active material and carbon nanotubes (with an outermost diameter of 0.1% by mass of the fiber (1.5 nm, fiber length (L) 12 μm) was mixed with 2% by mass of polyvinylidene fluoride as a binder, and then the mixture was mixed with N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry. Then, the slurry was mixed with a unit area weight of 250 g / m 2 The coating was applied on a positive electrode core formed of an aluminum foil with a thickness of 15 μm in a manner, and after the coating was dried, the coating was rolled using a calendering roller and cut into pieces with an outer diameter of The positive electrode having positive electrode mixture layers formed on both sides of the positive electrode core body is obtained by adjusting the electrode size of the outer shell to a predetermined value. It should be noted that an exposed portion where the surface of the positive electrode core body is exposed is provided at the upper end of the positive electrode.

[0093] [Production of negative electrode]

[0094] Natural graphite is used as the negative electrode active material. The negative electrode active material is mixed with sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode slurry. The negative electrode slurry is applied to both sides of a negative electrode core formed of copper foil, and after the coating film is dried, the coating film is rolled using a calendering roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a portion of the negative electrode.

[0095] [Preparation of non-aqueous electrolyte]

[0096] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed at a volume ratio of 3:3:4. Lithium hexafluorophosphate (LiPF6) was dissolved in the mixed solvent to a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0097] [Production of test battery cells]

[0098] 6 aluminum leads such as Figure 2 As shown, an aluminum lead is installed on the exposed portion of the positive electrode in a manner connected to the positive electrode at approximately equal intervals relative to the length direction of the positive electrode. In addition, a nickel lead is installed on the exposed portion of the negative electrode. The positive electrode and the negative electrode are spirally wound through a polyolefin separator to produce a wound electrode body. The electrode body is housed in an outer shell with an outer diameter of 50 mm, and after the non-aqueous electrolyte is injected, the opening at the upper end of the outer shell is sealed with a sealing body to obtain a test battery cell.

[0099] [Evaluation of volume energy density]

[0100] For the above test battery cell, under a temperature environment of 25°C, constant current charging is performed at 0.1It until the battery voltage becomes 4.2V, constant voltage charging is performed at 4.2V until the current value becomes 0.01It, and then constant current discharge is performed at 0.1It until the battery voltage becomes 2.5V. Furthermore, for the test battery cell, under a temperature environment of 25°C, constant current charging is performed at 0.1It until the battery voltage becomes 4.2V, constant voltage charging is performed at 4.2V until the current value becomes 0.01It, and then constant current discharge is performed at 0.2It until the battery voltage becomes 2.5V, and the discharge capacity at this time is taken as the initial discharge capacity. The initial discharge capacity is divided by the volume of the test battery cell to calculate the volume energy density. It should be noted that in the above charging and discharging, a 10-minute pause period is set when transferring from charging to discharging. The volume energy density of the test battery cell of Example 1 is 668Wh / L.

[0101] [Evaluation of internal resistance]

[0102] The test cell was charged at a constant current of 0.3 It at a temperature of 25°C until the cell voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current value reached 1 / 50 It. Next, the cell was discharged at a constant current of 1.0 It for 10 seconds, and the voltage drop at this time was divided by the current value to determine the internal resistance.

[0103] [Evaluation of capacity maintenance rate]

[0104] For the above test battery cell, in an environment of 25°C, charge at a constant current of 0.2It until the battery voltage reaches 4.2V, and then charge at a constant voltage of 4.2V until the current value reaches 0.01It. Thereafter, discharge at a constant current of 0.2It until the battery voltage reaches 2.5V. This charge and discharge is regarded as one cycle, and 300 cycles are performed. The capacity retention rate of the test battery cell in the charge and discharge cycle is calculated according to the following formula.

[0105] Capacity retention rate = (discharge capacity at the 300th cycle / discharge capacity at the 1st cycle) × 100

[0106] <Comparative Example 1>

[0107] A test cell was produced and evaluated in the same manner as in Example 1 except that Ca(OH) 2 , MoO 3 and WO 3 were not added in the production of the positive electrode active material.

[0108] <Comparative Example 2>

[0109] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 1 except that the number of aluminum lead wires was changed to one.

[0110] <Comparative Example 3>

[0111] In the production of the positive electrode, the weight per unit area is 200g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 1 except that the positive electrode slurry was applied in the manner of .

[0112] <Comparative Example 4>

[0113] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained, and in the production of the test battery cell, the electrode body is housed in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 1 except that an outer case of was used.

[0114] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Example 1 and Comparative Examples 1 to 4 are shown in Table 1. In addition, Table 1 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added element, the identified A x B y O z It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 1 are expressed relative to the values ​​of Comparative Example 1 as 100.

[0115] [Table 1]

[0116]

[0117] <Example 2>

[0118] A test battery cell was produced in the same manner as in Example 1 except that the following points were changed.

[0119] (1) In the mixing step of preparing the positive electrode active material, the composition of the lithium-containing composite oxide is LiNi 0.75 Co 0.10 Mn 0.15 O2.

[0120] (2) In the mixing step of preparing the positive electrode active material, Ca(OH)2, Sr(OH)2, WO3 and TiO2 were added in such a manner that the molar ratio of Ca, Sr, W and Ti was 0.2 mol% relative to the total amount of Ni, Co and Mn. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z Compounds, the presence of CaWO4 and SrTiO3 were confirmed.

[0121] (3) In the production of the positive electrode, the positive electrode is cut into a shape that can be accommodated in a In the production of the test battery cell, the electrode body is placed in the outer diameter of the specified electrode size of the outer shell. outer shell.

[0122] (4) In the production of the positive electrode, the weight per unit area is 275 g / m 2 The positive electrode slurry is coated in a manner.

[0123] (5) In the preparation of the positive electrode, the conductive material was changed from 0.1 mass % of carbon nanotubes (CNT) to 1.5 mass % of acetylene black (AB).

[0124] (6) During the production of the test battery cell, Figure 4 As shown, the positive electrode and the sealing body are connected via the positive electrode current collecting member.

[0125] <Comparative Example 5>

[0126] A test battery cell was produced and evaluated in the same manner as in Example 2 except that Ca(OH) 2 , Sr(OH) 2 , WO 3 and TiO 2 were not added during the production of the positive electrode active material.

[0127] <Comparative Example 6>

[0128] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 2 except that the number of aluminum lead wires was changed to one.

[0129] <Comparative Example 7>

[0130] In the production of the positive electrode, the weight per unit area is 190g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 2 except that the positive electrode slurry was applied in the manner of .

[0131] <Comparative Example 8>

[0132] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained, and in the production of the test battery cell, the electrode body is housed in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 2 except that the outer case was replaced with .

[0133] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Example 2 and Comparative Examples 5 to 8 are shown in Table 2. In addition, Table 2 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added element, the identified A x B y O z Compound, battery outer diameter, unit area weight of positive electrode mixture layer, current collection method of positive electrode and number of aluminum leads. It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 2 are expressed relative to the values ​​of Comparative Example 5 as 100.

[0134] [Table 2]

[0135]

[0136] <Example 3>

[0137] A test battery cell was produced in the same manner as in Example 1 except that the following points were changed.

[0138] (1) In the mixing step of preparing the positive electrode active material, the composition of the lithium-containing composite oxide is LiNi 0.80 Co 0.05 Mn 0.15 O2.

[0139] (2) In the mixing step of preparing the positive electrode active material, Sr(OH)2 and TiO2 were added so that the molar ratio of Sr to the total amount of Ni, Co and Mn was 0.2 mol% and the molar ratio of Ti was 0.2 mol%. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z The compound confirmed the presence of SrTiO3.

[0140] (3) In the production of the positive electrode, the positive electrode is cut into a shape that can be accommodated in a In the production of the test battery cell, the electrode body is placed in the outer diameter of the specified electrode size of the outer shell. outer shell.

[0141] (4) In the production of the positive electrode, the weight per unit area is 300 g / m2 The positive electrode slurry is coated in a manner.

[0142] (5) During the production of the test battery cell, Figure 3 As shown in FIG. 1 , the three aluminum leads are arranged so that the central angles formed by the radial direction lines passing through the circumferential centers of the three aluminum leads become substantially equal.

[0143] <Comparative Example 9>

[0144] A test battery cell was produced and evaluated in the same manner as in Example 3 except that Sr(OH) 2 and TiO 2 were not added during the production of the positive electrode active material.

[0145] <Comparative Example 10>

[0146] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 3 except that the number of aluminum lead wires was changed to one.

[0147] <Comparative Example 11>

[0148] In the production of the positive electrode, the weight per unit area is 200g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 3 except that the positive electrode slurry was applied in the manner of .

[0149] <Comparative Example 12>

[0150] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell has the specified electrode size, and the positive electrode and test battery cell are prepared by placing the electrode body in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 3 except that the outer case was replaced with .

[0151] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Example 3 and Comparative Examples 9 to 12 are shown in Table 3. In addition, Table 3 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added elements, the identified A x B y O z Compound, battery outer diameter, unit weight of positive electrode mixture layer, current collection method of positive electrode and number of aluminum leads. It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 3 are expressed relative to the values ​​of Comparative Example 9 as 100.

[0152] [Table 3]

[0153]

[0154] <Example 4>

[0155] A test battery cell was produced in the same manner as in Example 1 except that the following points were changed.

[0156] (1) In the mixing step of preparing the positive electrode active material, the composition of the lithium-containing composite oxide is LiNi 0.80 Co 0.10 Mn 0.10 O2.

[0157] (2) In the mixing step of preparing the positive electrode active material, Ca(OH)2 and MoO3 were added to the above metal oxides in such a manner that the molar ratio of Ca to the total amount of Ni, Co and Mn was 0.2 mol% and the molar ratio of Mo was 0.2 mol%. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z The compound confirmed the presence of CaMoO4.

[0158] (3) In the production of the positive electrode, the weight per unit area is 325 g / m 2 The positive electrode slurry is coated in a manner.

[0159] (4) During the production of the test battery cell, Figure 2 As shown, three aluminum leads are connected to the positive electrode at substantially equal intervals in the longitudinal direction of the positive electrode.

[0160] <Comparative Example 13>

[0161] A test cell was produced and evaluated in the same manner as in Example 4 except that Ca(OH) 2 and MoO 3 were not added during the production of the positive electrode active material.

[0162] <Comparative Example 14>

[0163] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 4 except that the number of aluminum lead wires was changed to one.

[0164] <Comparative Example 15>

[0165] In the production of the positive electrode, the weight per unit area is 200g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 5 except that the positive electrode slurry was applied in the manner of .

[0166] <Comparative Example 16>

[0167] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained, and in the production of the test battery cell, the electrode body is housed in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 4 except that the outer casing was replaced with .

[0168] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Example 4 and Comparative Examples 13 to 16 are shown in Table 4. In addition, Table 4 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added element, the identified A x B y O z Compound, battery outer diameter, unit weight of positive electrode mixture layer, current collection method of positive electrode and number of aluminum leads. It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 4 are expressed relative to the values ​​of Comparative Example 13 as 100.

[0169] [Table 4]

[0170]

[0171] <Example 5>

[0172] A test battery cell was produced in the same manner as in Example 1 except that the following points were changed.

[0173] (1) In the mixing step of preparing the positive electrode active material, the composition of the lithium-containing composite oxide is LiNi 0.85 Co 0.05 Mn 0.10 O2.

[0174] (2) In the mixing step of preparing the positive electrode active material, Ca(OH)2 and TiO2 were added to the above metal oxides in such a manner that the molar ratio of Ca to the total amount of Ni, Co and Mn was 0.2 mol% and the molar ratio of Ti was 0.2 mol%. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z The presence of CaTiO4 was confirmed.

[0175] (3) In the production of the positive electrode, the positive electrode is cut into a shape that can be accommodated in a In the production of the test battery cell, the electrode body is placed in the outer diameter of the specified electrode size of the outer shell. outer shell.

[0176] (4) In the production of the positive electrode, the weight per unit area is 350 g / m2 The positive electrode slurry is coated in a manner.

[0177] (5) During the production of the test battery cell, Figure 4 As shown, the positive electrode and the sealing body are connected via the positive electrode current collecting member.

[0178] <Comparative Example 17>

[0179] A test battery cell was produced and evaluated in the same manner as in Example 5 except that Ca(OH) 2 and TiO 2 were not added during the production of the positive electrode active material.

[0180] <Comparative Example 18>

[0181] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 5 except that the number of aluminum lead wires was changed to one.

[0182] <Comparative Example 19>

[0183] In the production of the positive electrode, the weight per unit area is 225g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 5 except that the positive electrode slurry was applied in the manner of .

[0184] <Comparative Example 20>

[0185] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained, and in the production of the test battery cell, the electrode body is housed in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 5 except that the outer case was replaced with .

[0186] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Example 5 and Comparative Examples 17 to 20 are shown in Table 5. In addition, Table 5 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added element, the identified A x B y O z Compound, battery outer diameter, unit weight of positive electrode mixture layer, current collection method of positive electrode and number of aluminum leads. It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 5 are expressed relative to the values ​​of Comparative Example 17 as 100.

[0187] [Table 5]

[0188]

[0189] <Example 6>

[0190] A test battery cell was produced in the same manner as in Example 1 except that the following points were changed.

[0191] (1) In the mixing step of preparing the positive electrode active material, the composition of the lithium-containing composite oxide is LiNi 0.90 Co 0.05 Mn 0.05 O2.

[0192] (2) In the mixing step of preparing the positive electrode active material, Ca(OH)2 and ZrO2 were added to the above metal oxides in such a manner that the molar ratio of Ca to the total amount of Ni, Co and Mn was 0.2 mol% and the molar ratio of Zr was 0.2 mol%. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z The presence of CaZrO3 was confirmed.

[0193] (3) In the production of the positive electrode, the positive electrode is cut into a shape that can be accommodated in a In the production of the test battery cell, the electrode body is placed in the outer diameter of the specified electrode size of the outer shell. outer shell.

[0194] (4) In the preparation of the positive electrode, the conductive material was changed from 0.1 mass % of carbon nanotubes (CNT) to 1.5 mass % of acetylene black (AB). Furthermore, 5 mass % of Li2NiO2 was added.

[0195] (5) During the production of the test battery cell, Figure 2 As shown, four aluminum leads are connected to the positive electrode at substantially equal intervals in the longitudinal direction of the positive electrode.

[0196] <Comparative Example 21>

[0197] A test battery cell was produced and evaluated in the same manner as in Example 6 except that Ca(OH) 2 and ZrO 2 were not added during the production of the positive electrode active material.

[0198] <Comparative Example 22>

[0199] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 6 except that the number of aluminum lead wires was changed to one.

[0200] <Comparative Example 23>

[0201] In the production of the positive electrode, the weight per unit area is 225g / m 2A test battery cell was prepared and evaluated in the same manner as in Example 6 except that the positive electrode slurry was applied in the manner of .

[0202] <Comparative Example 24>

[0203] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained. In the production of the test battery cell, the electrode body is placed in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 6 except that the outer case was replaced with .

[0204] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Example 6 and Comparative Examples 21 to 24 are shown in Table 6. In addition, Table 6 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added element, the identified A x B y O z It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 6 are expressed relative to the values ​​of Comparative Example 21 as 100.

[0205] [Table 6]

[0206]

[0207] <Example 7>

[0208] A test battery cell was produced in the same manner as in Example 1 except that the following points were changed.

[0209] (1) In the mixing step of preparing the positive electrode active material, the composition of the lithium-containing composite oxide is LiNi 0.90 Co 0.025 Mn 0.075 O2.

[0210] (2) In the mixing step of preparing the positive electrode active material, Sr(OH)2 and ZrO2 were added to the above metal oxides in such a manner that the molar ratio of Sr to the total amount of Ni, Co and Mn was 0.2 mol% and the molar ratio of Zr was 0.2 mol%. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z The presence of SrZrO3 was confirmed.

[0211] (3) In the production of the positive electrode, the positive electrode is cut into a shape that can be accommodated in a The electrode body is placed in the outer diameter of the outer shell of the test battery cell. outer shell.

[0212] (4) In the production of the positive electrode, the weight per unit area is 300 g / m 2 The positive electrode slurry is coated in a manner.

[0213] (5) In the preparation of the positive electrode, in addition to 0.1 mass % of carbon nanotubes (CNT) as a conductive material, 5 mass % of Li2NiO2 was added.

[0214] (6) During the production of the test battery cell, Figure 4 As shown, the positive electrode and the sealing body are connected via the positive electrode current collecting member.

[0215] <Example 8>

[0216] In the mixing step of preparing the positive electrode active material, Ca(OH)2 and ZrO2 were added to the above metal oxides so that the molar ratio of Ca to the total amount of Ni, Co and Mn was 0.2 mol% and the molar ratio of Zr was 0.2 mol%. A test battery cell was prepared and evaluated in the same manner as in Example 7. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z The presence of CaZrO3 was confirmed.

[0217] <Comparative Example 25>

[0218] A test battery cell was produced and evaluated in the same manner as in Example 7 except that Sr(OH) 2 and ZrO 2 were not added during the production of the positive electrode active material.

[0219] <Comparative Example 26>

[0220] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 7 except that the number of aluminum lead wires was changed to one.

[0221] <Comparative Example 27>

[0222] In the production of the positive electrode, the weight per unit area is 225g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 7 except that the positive electrode slurry was applied in the manner of .

[0223] <Comparative Example 28>

[0224] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained, and in the production of the test battery cell, the electrode body is housed in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 7 except that the outer casing was replaced with .

[0225] <Comparative Example 29>

[0226] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 8 except that the number of aluminum lead wires was changed to one.

[0227] <Comparative Example 30>

[0228] In the production of the positive electrode, the weight per unit area is 225g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 8 except that the positive electrode slurry was applied in a manner of .

[0229] <Comparative Example 31>

[0230] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained, and in the production of the test battery cell, the electrode body is housed in the outer diameter A test battery cell was produced and evaluated in the same manner as in Example 8 except that the outer casing was replaced with .

[0231] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Examples 7 and 8 and Comparative Examples 25 to 31 are shown in Table 7. In addition, Table 7 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added element, the identified A x B y O z Compound, battery outer diameter, unit area weight of positive electrode mixture layer, current collection method of positive electrode and number of aluminum leads. It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 7 are expressed relative to the values ​​of Comparative Example 25 as 100.

[0232] [Table 7]

[0233]

[0234] <Example 9>

[0235] A test battery cell was produced in the same manner as in Example 1 except that the following points were changed.

[0236] (1) In the mixing step of preparing the positive electrode active material, the composition of the lithium-containing composite oxide is LiNi 0.90 Co 0.035 Mn 0.065 O2.

[0237] (2) In the mixing step of preparing the positive electrode active material, Ca(OH)2, Sr(OH)2, TiO2 and ZrO2 were added in such a manner that the molar ratio of Ca, Sr, Ti and Zr relative to the total amount of Ni, Co and Mn was 0.2 mol%, 0.2 mol%, 0.2 mol%, and 0.2 mol%. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z Compounds, the presence of CaZrO3 and SrTiO3 were confirmed.

[0238] (3) In the production of the positive electrode, the weight per unit area is 325 g / m 2 The positive electrode slurry is coated in a manner.

[0239] (4) During the production of the test battery cell, Figure 4 As shown, the positive electrode and the sealing body are connected via the positive electrode current collecting member.

[0240] <Comparative Example 32>

[0241] A test battery cell was produced and evaluated in the same manner as in Example 9 except that Ca(OH) 2 , Sr(OH) 2 , TiO 2 and ZrO 2 were not added during the production of the positive electrode active material.

[0242] <Comparative Example 33>

[0243] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 9 except that the number of aluminum lead wires was changed to one.

[0244] <Comparative Example 34>

[0245] In the production of the positive electrode, the weight per unit area is 225g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 9 except that the positive electrode slurry was applied in the manner of .

[0246] <Comparative Example 35>

[0247] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained, and in the production of the test battery cell, the electrode body is housed in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 9 except that the outer casing was replaced with .

[0248] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Example 9 and Comparative Examples 32 to 35 are shown in Table 8. In addition, Table 8 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added element, the identified A x B y O z Compound, battery outer diameter, unit area weight of positive electrode mixture layer, current collection method of positive electrode and number of aluminum leads. It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 8 are expressed relative to the values ​​of Comparative Example 32 as 100.

[0249] [Table 8]

[0250]

[0251] <Example 10>

[0252] A test battery cell was produced in the same manner as in Example 1 except that the following points were changed.

[0253] (1) In the mixing step of preparing the positive electrode active material, the composition of the lithium-containing composite oxide is LiNi 0.925 Mn 0.075 O2.

[0254] (2) In the mixing step of preparing the positive electrode active material, Sr(OH)2 and ZrO2 were added in such a manner that the molar ratio of Sr was 0.2 mol% and the molar ratio of Zr was 0.2 mol% relative to the total amount of Ni and Mn. In addition, the compounds present in the positive electrode active material were identified by synchrotron X-ray diffraction measurement, and the results were as follows: x B y O z The presence of SrZrO3 was confirmed.

[0255] (3) In the production of the positive electrode, the positive electrode is cut into a shape that can be accommodated in a In the production of the test battery cell, the electrode body is placed in the outer diameter of the specified electrode size of the outer shell. outer shell.

[0256] (4) In the production of the positive electrode, the weight per unit area is 350 g / m 2 The positive electrode slurry is coated in a manner.

[0257] (5) During the production of the test battery cell, Figure 4As shown, the positive electrode and the sealing body are connected via the positive electrode current collecting member.

[0258] <Comparative Example 36>

[0259] A test battery cell was produced and evaluated in the same manner as in Example 10 except that Sr(OH) 2 and ZrO 2 were not added during the production of the positive electrode active material.

[0260] <Comparative Example 37>

[0261] In the preparation of the test cell, a test cell was prepared and evaluated in the same manner as in Example 10 except that the number of aluminum lead wires was changed to one.

[0262] <Comparative Example 38>

[0263] In the production of the positive electrode, the weight per unit area is 225g / m 2 A test battery cell was prepared and evaluated in the same manner as in Example 10 except that the positive electrode slurry was applied in the manner of .

[0264] <Comparative Example 39>

[0265] In the production of the positive electrode, the electrode is cut into a shape that fits into a The outer shell of the electrode body has a predetermined electrode size, and the positive electrode is obtained, and in the production of the test battery cell, the electrode body is housed in the outer diameter A test battery cell was prepared and evaluated in the same manner as in Example 10 except that the outer case was replaced with .

[0266] The volume energy density, internal resistance and capacity retention rate of the test battery cells of Example 10 and Comparative Examples 36 to 39 are shown in Table 9. In addition, Table 9 also shows the composition of the lithium-containing composite oxide (the ratio of each metal element to the total molar number of metal elements other than Li), the type and amount of the added element, the identified A x B y O z It should be noted that the volume energy density, internal resistance and capacity retention rate shown in Table 9 are expressed relative to the values ​​of Comparative Example 36 as 100.

[0267] [Table 9]

[0268]

[0269] In any of Tables 1 to 9, the Examples all maintain a high volume energy density compared to the Comparative Examples, and all have both low internal resistance and high capacity retention. That is, by making the unit area weight of the positive electrode mixture layer containing the positive electrode active material 250 g / m2 As described above, by connecting the positive electrode and the sealing body in a predetermined manner and using a positive electrode active material having a surface modification layer, a high energy density can be achieved, and the power characteristics and cycle characteristics can be improved.

[0270] The present disclosure is further described by the following embodiments.

[0271] Configuration 1: A non-aqueous electrolyte secondary battery, comprising: an electrode body formed by stacking a positive electrode and a negative electrode with a separator therebetween, and an outer shell for accommodating the electrode body, wherein the volume energy density of the non-aqueous electrolyte secondary battery is 600Wh / L or more, the positive electrode comprising: a positive electrode core, and a positive electrode mixture layer formed on the surface of the positive electrode core and containing a positive electrode active material, the positive electrode active material comprising: a lithium-containing composite oxide having a layered rock salt structure, and a surface modification layer present on the surface of particles of the composite oxide, the surface modification layer comprising at least one element of Ca and Sr and comprising at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, and the unit area weight of the positive electrode mixture layer is 250g / m 2 As mentioned above, three or more positive electrode leads are connected to the positive electrode.

[0272] Configuration 2: The nonaqueous electrolyte secondary battery according to Configuration 1, wherein the outer casing has a bottomed cylindrical shape with an outer diameter of 25 mm or more.

[0273] Configuration 3: The nonaqueous electrolyte secondary battery according to Configuration 1 or 2, wherein the three or more positive electrode leads are arranged at substantially equal intervals along the longitudinal direction of the positive electrode.

[0274] Configuration 4: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein the three or more positive electrode leads are arranged so that central angles formed by radial lines passing through circumferential centers of the positive electrode leads are substantially equal.

[0275] Configuration 5: A non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein a plurality of exposed portions in which a portion of the positive electrode core is exposed in a width direction are provided along the length direction of the positive electrode, the positive electrode mixture layer is present between the exposed portions throughout the width direction, and one of the positive electrode leads is connected to each of the exposed portions.

[0276] Configuration 6: A non-aqueous electrolyte secondary battery, comprising: an electrode body formed by stacking a positive electrode and a negative electrode with a separator therebetween, and an outer shell for accommodating the electrode body, wherein the volume energy density of the non-aqueous electrolyte secondary battery is 600Wh / L or more, the positive electrode comprising: a positive electrode core, and a positive electrode mixture layer formed on the surface of the positive electrode core and containing a positive electrode active material, the positive electrode active material comprising: a lithium-containing composite oxide having a layered rock salt structure, and a surface modification layer present on the surface of particles of the composite oxide, the surface modification layer comprising at least one element of Ca and Sr and comprising at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, and the unit area weight of the positive electrode mixture layer is 250g / m 2 In the above, the end of the positive electrode core is connected to the positive electrode current collecting member, and the positive electrode lead is connected to the positive electrode current collecting member.

[0277] Configuration 7: The nonaqueous electrolyte secondary battery according to Configuration 6, wherein the outer casing has a bottomed cylindrical shape with an outer diameter of 25 mm or more.

[0278] Configuration 8: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the surface modification layer comprises a compound of the general formula A x B y O z (wherein, 1≤x≤2, 1≤y≤5, 4≤z≤9, A is at least one selected from Ca and Sr, and B is at least one selected from W, Mo, Ti, Si, Nb and Zr).

[0279] Configuration 9: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 8, wherein the positive electrode mixture layer contains carbon fibers, and a content of the carbon fibers is 0.01 mass % or more and 1 mass % or less relative to the mass of the positive electrode active material.

[0280] Configuration 10: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 9, wherein the positive electrode mixture layer contains amorphous carbon, and a content of the amorphous carbon is 1 mass % or more and 3 mass % or less relative to the mass of the positive electrode active material.

[0281] Configuration 11: The nonaqueous electrolyte secondary battery according to claim 1 or 6, wherein the content of Ni in the lithium-containing composite oxide is 70 mol % or more relative to the total amount of metal elements other than Li.

[0282] Configuration 12: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 10, wherein the positive electrode mixture layer contains Li 2 NiO 2 .

[0283] Configuration 13: The non-aqueous electrolyte secondary battery according to Configuration 12, wherein the content of Li2NiO2 contained in the positive electrode mixture layer is 1% by mass or more and 10% by mass or less relative to the total mass of the positive electrode active material.

[0284] Configuration 14: The non-aqueous electrolyte secondary battery according to any one of Configurations 1 to 13, wherein the positive electrode mixture layer contains a compound represented by the general formula Li a Ni 2-a O2 (0 < a ≤ 0.5).

[0285] Configuration 15: The non-aqueous electrolyte secondary battery according to Configuration 14, wherein the content of the compound represented by the general formula Li a Ni 2-a O2 (0 < a ≤ 0.5) contained in the positive electrode mixture layer is 0.1% by mass or more and 5% by mass or less relative to the total mass of the positive electrode active material.

[0286] Explanation of Reference Numerals

[0287] 10 Non-aqueous electrolyte secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 15 Outer casing, 16 Sealing body, 17, 18 Insulating plate, 19 Positive electrode lead, 20 Negative electrode lead, 21 Groove portion, 22 Locally open metal plate, 23 Lower valve body, 24 Insulating member, 25 Upper valve body, 26 Cover, 27 Gasket, 30 Positive electrode core, 32 Positive electrode mixture layer, 34, 44 Exposed portion, 40 Negative electrode core, 42 Negative electrode mixture layer, 50 Positive electrode current collector member.

Claims

1. A non-aqueous electrolyte secondary battery comprising: An electrode body in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween, and an outer shell housing the electrode body, The volume energy density of the non-aqueous electrolyte secondary battery is 600Wh / L or more. The positive electrode comprises: a positive electrode core body, and a positive electrode mixture layer formed on a surface of the positive electrode core body and containing a positive electrode active material. The positive electrode active material comprises: a lithium-containing composite oxide having a layered rock salt structure, and a surface modification layer present on the surface of the composite oxide particles. The surface modification layer contains at least one element of Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. The unit area weight of the positive electrode mixture layer is 250 g / m 2 above, The positive electrode is connected to three or more positive electrode leads.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The outer shell has a bottomed cylindrical shape with an outer diameter of 25 mm or more.

3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The positive electrode leads are arranged at substantially equal intervals along the longitudinal direction of the positive electrode.

4. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The positive electrode lead is arranged so that the central angles formed by the radial direction lines passing through the circumferential center of the positive electrode lead are substantially equal.

5. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: A plurality of exposed portions are provided along the length direction of the positive electrode, where a portion of the positive electrode core is exposed in the width direction. The positive electrode mixture layer is present between the exposed portions in the width direction. One of the positive electrode leads is connected to each of the exposed portions.

6. A non-aqueous electrolyte secondary battery comprising: An electrode body in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween, and an outer shell housing the electrode body, The volume energy density of the non-aqueous electrolyte secondary battery is 600Wh / L or more. The positive electrode comprises: a positive electrode core body, and a positive electrode mixture layer formed on a surface of the positive electrode core body and containing a positive electrode active material. The positive electrode active material comprises: a lithium-containing composite oxide having a layered rock salt structure, and a surface modification layer present on the surface of the composite oxide particles. The surface modification layer contains at least one element of Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. The unit area weight of the positive electrode mixture layer is 250 g / m 2 above, The end of the positive electrode core is connected to a positive electrode current collecting component, and a positive electrode lead is connected to the positive electrode current collecting component.

7. The nonaqueous electrolyte secondary battery according to claim 6, wherein The outer shell has a bottomed cylindrical shape with an outer diameter of 25 mm or more.

8. The nonaqueous electrolyte secondary battery according to claim 1 or 6, wherein The surface modification layer comprises the general formula A x B y O z The compound shown in the formula, wherein 1≤x≤2, 1≤y≤5, 4≤z≤9, A is at least one selected from Ca and Sr, and B is at least one selected from W, Mo, Ti, Si, Nb and Zr.

9. The nonaqueous electrolyte secondary battery according to claim 1 or 6, wherein: The positive electrode mixture layer includes carbon fibers, and a content of the carbon fibers is 0.01 mass % or more and 1 mass % or less relative to the mass of the positive electrode active material.

10. The nonaqueous electrolyte secondary battery according to claim 1 or 6, wherein: The positive electrode mixture layer includes amorphous carbon, and a content of the amorphous carbon is 1 mass % or more and 3 mass % or less relative to the mass of the positive electrode active material.

11. The nonaqueous electrolyte secondary battery according to claim 1 or 6, wherein: The content of Ni in the lithium-containing composite oxide is 70 mol % or more relative to the total amount of metal elements excluding Li.

12. The nonaqueous electrolyte secondary battery according to claim 1 or 6, wherein: The positive electrode mixture layer contains Li2NiO2.

13. The nonaqueous electrolyte secondary battery according to claim 12, wherein: The content of Li2NiO2 contained in the positive electrode mixture layer is greater than or equal to 1% by mass and less than or equal to 10% by mass relative to the total mass of the positive electrode active material.

14. The nonaqueous electrolyte secondary battery according to claim 1 or 6, wherein: The positive electrode mixture layer comprises a general formula Li a Ni 2-a O2, wherein 0 <a≤0.5。 15. The nonaqueous electrolyte secondary battery according to claim 14, wherein The positive electrode mixture layer contains the general formula Li a Ni 2-a The content of the compound represented by O2 is 0.1 mass % or more and 5 mass % or less relative to the total mass of the positive electrode active material, wherein 0 <a≤0.5。

Citation Information

Patent Citations

  • Sequentially actuating valve assembly by pressure

    JP1982047082A

  • Method and network unit for realizing customized video service in IMS network

    WO2010000106A1